The Association of Socioeconomic Characteristics with Psychological Distress and Burnout in Disability Assistance Cadres in Bandung - Athifah, Nur Azizah Arif; Lukman Hilfi; Sri Yusnita Irda Sari (CV Media Inti Teknologi, 2025)
People with disabilities risk facing obstacles in participating in and benefiting from development. Indonesia is committed to supporting people with disabilities, one of which is through services and rehabilitation provided by cadres. Unfortunately, there is currently no regulation governing compensation for cadres that puts them at risk of psychological distress and burnout. This research intends to analyze the association of different socioeconomic characteristics with psychological distress and burnout and the association between the two conditions in cadres providing services in Bandung City. Through a secondary cross-sectional research, 648 cadres’ data were obtained. The data included were socioeconomic characteristics, psychological distress (Kessler-10), and burnout (The Burnout Measure Short Version). This article discovered a significant negative correlation between age (ρ = -0.097; p = 0.014) and seniority (ρ = -0.134; p < 0.001) toward psychological distress and a significant positive correlation between psychological distress and burnout (ρ = 0.505; p < 0.001). These findings highlight the importance of considering age and seniority to support cadres' mental health and ensure a sustainable recruitment and regeneration strategy.